2005
DOI: 10.1021/cm0518372
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a TiO2 Micronetwork on a UV-Absorbing SiO2-Based Glass Surface by Excimer Laser Irradiation

Abstract: We report on the preparation of TiO2 micronetworks on a UV-absorbing Na2O−TiO2−SiO2 glass surface by excimer laser irradiation, a technique we have called laser-induced superficial phase separation. The TiO2 micronetworks that were formed on the etched glass surface were in the rutile crystalline phase and exhibited a photocatalytic capability. We were also able to form a range of TiO2 micronetworks in an array of 20-μm holes. This flexible formation of photocatalytic TiO2 networks on a glass surface without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We confirmed that the TiO 2 micronetworks were precipitated in the rutile crystalline phase and that they exhibited photocatalytic capability [8]. Utilizing this technique, we can make patterning of crystalline TiO 2 micronetworks on glass surfaces without the application of any heat treatments and/or adhesives.…”
Section: Introductionsupporting
confidence: 57%
“…We confirmed that the TiO 2 micronetworks were precipitated in the rutile crystalline phase and that they exhibited photocatalytic capability [8]. Utilizing this technique, we can make patterning of crystalline TiO 2 micronetworks on glass surfaces without the application of any heat treatments and/or adhesives.…”
Section: Introductionsupporting
confidence: 57%
“…The photoinduced phase transformation of orthorhombic CdS nanoparticles is spectrally selective; the nanoparticles change to the hexagonal form during irradiation by light with l = 355 nm and to the cubic form with l = 532 nm [286,287]. It was found that the crystallization of amorphous TiO 2 [77,288] and Ge [289] nanoparticles takes place under the influence of laser light.…”
Section: Formation Of Semiconductor Nanoparticles and Change Of Theirmentioning
confidence: 99%
“…[74][75][76][77][78][79][80][81][82]. Thus, during the irradiation of a dimethylsiloxane and styrene block copolymer with UV light on the surface of the nanostructured TiO 2 films selective oxidation of the polystyrene sections occurs, and the polysiloxane is simultaneously transformed into SiO 2 nanoparticles, leading to the formation of periodic silica structures on the surface of the TiO 2 film [74].…”
Section: Photochemical Production Of Nanostructured Metal Oxidesmentioning
confidence: 99%
“…[1][2][3] Various oxide lms have been formed on polymer substrates to achieve their functionality. [4][5][6][7] In particular, patterning of oxide thin lms is of great signicance in the development of sensor arrays, 8 memory arrays, 9 integrated electronics, 10 solar cell, 11 and so forth. In general, the formation for such oxide thin lms should be conducted in mild conditions to remain the optical and mechanical properties of polymer substrate, therefore, the traditional micropatterning strategies involving erosive chemicals or high temperature conditions are no longer favoured.…”
Section: Introductionmentioning
confidence: 99%